A CFD model for predicting protein aggregation in low‐pH virial inactivation for mAb production. Issue 11 (28th July 2020) - Xing, Zizhuo; Jin, Weixin; Xu, Xuankuo; Song, Yuanli; Huang, Chao; Borys, Michael C.; Ghose, Sanchayita; Li, Zheng Jian
Abstract: Significant amounts of soluble product aggregates were observed in the low‐pH viral inactivation (VI) operation during an initial scale‐up run for an immunoglobulin‐G 4 (IgG4) monoclonal antibody (mAb IgG4‐N1). Being earlier in development, a scale‐down model did not exist, nor was it practical to use costly Protein A eluate (PAE) for testing the VI process at scale, thus, a computational fluid dynamics (CFD)‐based high‐molecular weight (HMW) prediction model was developed for troubleshooting and risk mitigation. It was previously reported that the IgG4‐N1 molecules upon exposure to low pH tend to change into transient and partially unfolded monomers during VI acidification (i.e., VIA) and form aggregates after neutralization (i.e., VIN). Therefore, the CFD model reported here focuses on the VIA step. The model mimics the continuous addition of acid to PAE and tracks acid distribution during VIA. Based on the simulated low‐pH zone (≤pH 3.3) profiles and PAE properties, the integrated low‐pH zone (ILPZ) value was obtained to predict HMW level at the VI step. The simulations were performed to examine the operating parameters, such as agitation speed, acid addition rate, and protein concentration of PAE, of the pilot scale (50–200 L) runs. The conditions with predictions of no product aggregation risk were recommended to the real scale‐up runs, resulted in 100% success rate of the consecutive 12 pilot‐scale runs. This study demonstrated that the CFD‐based HMW prediction model could be used as a tool to facilitate the scale up of the low‐pH VI process directly from bench to pilot/production scale. Abstract : A novel protein viral inactivation simulation model was developed in this study, which incorporates computaninal fluid dynamics (CFD) simulation under an operating condition and the molecular specific aggregation property to predict high molecular weight (HMW) formation. The model provides potential applications in scale‐up of the low‐pH viral inactivation process directly from bench to pilot/production scale to mitigate excessive HMW formation for a pH sensitive protein.